Inventory and habitat study of orchids species in Lamedai Nature Reserve, Kolaka, Southeast Sulawesi - DEWI AYU LESTARI; WIDJI SANTOSO (Biodiversitas Journal of Biological Diversity, 2011)
Lestari DA, Santoso W (2011) Inventory and habitat study of orchids species in Lamedai Nature Reserve, Kolaka, Southeast Sulawesi. Biodiversitas 12: 28-33. Orchid is one of the ornamental plants which have been high commercial value. Therefore, orchid often has been over exploitation. Finally, some of orchid species are becoming threatened or even endangered. Purwodadi Botanical Garden as an institute of ex-situ conservation play role with it. The aim of this research is to inventory orchid’s species in Lamedai Nature Reserve, Kolaka, Southeast Sulawesi by explorative method. Observation for habitat study was focused on some ecological factors supported to orchids growth like host tree, zone growth on host tree, abundance of sunlight, thickness of substrate (moss), orchid species and number of individual species. The result showed that there were 27 orchids species, consist of, 25 species (16 genera) epiphytic orchid and 2 species terrestrial orchid such as Eulophia keithii var. celebica and Goodyera rubicunda (Blume) Lindl. The host preference for theepiphytic orchid is the group of Myrtaceae family like Syzygium sp., Metrosideros vera Niederen and Metrosideros sp. They mostly grow on the main stem of the tree zone 1 on thick substrate (moss) and get a little abundance of sunlight (calm).